RESULTS OF COMBINED TREATMENT WITH INTRAOPERATIVE RADIAL THERAPY OF SOFT TISSUE SARCOMA - P. A. Ott; A. V. Privalov; A. V. Vazhenin; N. A. Chekha; E. G. Zabolotskaya; A. V. Komissarov (Вестник хирургии имени И.И. Грекова)
The intraoperative radiation therapy (IORT) in combined therapy of soft tissue sarcoma in a single dose 10–20 Gy is the method, which can optimize the role of radiation therapy in treatment of this nosology. This method allows exact localization of the irradiation zone in the frames of «tumor bed», thereby minimizing the damage of normal tissues and critical organs. The aim of the study was the influence of IORT on the rate and structure of postoperative complications and long-term results of treatment in the group under study (n=49) in comparison with the group of combined treatment without IORT (n=57) and the group of surgical treatment. No statistically reliable difference in the rate of postoperative complications in groups (p=0.57) was obtained and there was no influence on the structure of postoperative complications. At the same time the statistically reliable increase of general survival rates (p=0.025) and the survival without relapse in the main group (p